Pengaruh Perputaran Kas, Perputaran Piutang dan Perputaran Persediaan terhadap Return On Asset pada Perusahaan Sub Sektor Semen yang Terdaftar dalam Bursa Efek Indonesia Periode Tahun 2013-2023 - Rahmawati, Gina; Priyanto, Aria Aji (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
The purpose of this study is to determine the level of cash turnover, receivables turnover and inventory turnover have an influence on return on assets in a company. The object of this study is a cement sub-sector company listed on the Indonesia Stock Exchange for the period 2013-2023. The type of data in this study is quantitative with an associative method. The data source in this study is secondary data with a sample size of 44, namely 4 cement sub-sector companies listed on the Indonesia Stock Exchange and financial report data for the period 2013-2023 related to the variables in the study. The findings reveal that cash turnover and inventory turnover do not have a significant effect on ROA, whereas receivables turnover shows a significant positive influence. Simultaneously, the three variables exert a positive and significant effect on ROA, as reflected in the regression equation Y = -0.842982+0.145359 * X1+0.177113 * X2+1.063431* X3, with a coefficient of determination of 51.17%. This implies that 48.83% of the variation in ROA is explained by other factors not included in the model. Overall, the results highlight the importance of efficient receivables management in enhancing company profitability within the cement industry.